Significant Factors Causing Delay of Ethiopian Road Construction Projects performing by Foreign General Contactors - Darsa, Mohammadzen Hasan; Negash, Biniyam Tsegu (International Journal of Sustainable Construction Engineering and Technology, 2023)
Following the booming of the Ethiopian construction industry, a number of Foreign General Contractors (FGCs) are participating in the industry. The severity of the construction projects schedule delay, which is a worldwide problem also, affecting the FGCs participating in the Ethiopian road construction projects. Identifying the challenging factors affect the project performance was an important and initial stage for improving the project progress. This study identified the significant factors that cause the projects schedule delay systematically and objectively. After 30 factors were determined from literature and pilot survey, the final questionnaire survey of 235 domain experts was conducted to systematically select 20 factors. Based on the 20 selected factors, 81 historical data of road construction projects with schedule delay were collected; and the database was established. The artificial neural network (ANN) inference model was developed to train the database and predict the project schedule delay. Integrating it with the Garson algorithm (GA), the relative weights of challenging factors with rankings were calculated and identified. The top ten significant factors identified were Contractor’s poor site management; Ineffective planning, scheduling, controlling and quality monitoring; Difficulty in Budget availability for the project; Delays in construction activities due to weather changes; late land acquisition; Shortage of materials; Financial problem of contractors; Poor supervision; Cash-flow problems (irregular payments), and Financial Capability of Client. This study uses as a significant reference for FGCs who are currently working in the Ethiopian Road construction projects for improving the projects schedule performance.